Infrastucture : finance, provosion and operation - Seminar on Infrasturcture : Finance, Provision and Operation (1997 : Brunel University, England); PTRC European Transport Forum Annual Meeting (25th : 1997 : Brunel University, England) (London : PTRC Education and Research Services, 1997)
08